STRATEGI GURU DALAM PENGUATAN KEMAMPUAN LITERASI DAN NUMERASI PADA SISWA KELAS V DI SD NEGERI SERDANG WETAN - Sina, Noni; Nurul Febrianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the fact that the school did not have a library room, lacked a variety of reading materials, and not all classrooms had a reading corner. There are extracurricular activities conducted by students, such as scouting and pencak silat, which involve skills in measuring tents, distances, and time. However, these skills in literacy and numeracy are not well mastered. The purpose of this study is to determine the strategies teachers use to strengthen literacy skills and to identify the strategies teachers employ to enhance numeracy skills among fifth-grade students. The data collection techniques used were observation, interviews and documentation. In addition, the data analysis procedure used was data collection, data reduction, data presentation, and conclusion drawing. The results of the study on teachers’ strategies in strengthening literacy skills in fifth-grade students are: (1) Literacy projects, (2) Reading culture promoted by teachers, (3) Habit-forming activities in the classroom, (4) Extracurricular activities such as scouting and pencak silat, and (5) School programs. The strategies employed by teachers to strengthen numeracy skills among fifth-grade students include: (1) Numeracy projects, (2) Reading culture promoted by teachers, (3) Routine activities in the classroom, (4) Extracurricular activities such as scouting and pencak silat, and (5) Schools program activities.